(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Achievement of an effective balance between government regulation of business and free competition is the goal of any progressive economy, and attention to this issue is completely justified. This study aims to analyze the concept of administration and "market phenomenon: the collision of coexistence in territorial economy. To do so, the systemic, institutional, reproductive approaches are utilized. Based on the results, the need for a constructive solution to this problem leads to a logical conclusion about the need to create an administrative and economic system to regulate social practice of a new type, based on the principles of maximizing freedom of expression and economic initiative within the boundaries of social expediency. This regulatory system presupposes the presence of continuous monitoring of reproduction processes, the timely identification of constraints on the implementation of the economic strategy and an urgent corrective administrative and economic impact on these elements. The solution to this problem seems possible through the multi-level implementation of BIM technologies in economic administration within the Russian territorial and economic practice, built on the principles of network modeling of the reproduction process.